Synthesis of Novel N-Sulfonyl Monocyclic β-Lactams as Potential Antibacterial Agents - Jarrahpour, Aliasghar (Molecules, 2006)
New cis monocyclic β-lactams were synthesized by [2+2] Staudinger cycloaddition reactions of the imine (3,4-dimethoxybenzylidene)-(4-methoxyphenyl)-amine and ketenes derived from different acyl chlorides and Et(3)N. These monocyclic β-lactams were then cleaved by ceric ammonium nitrate (CAN) to give NH-monocyclic β-lactams, which in turn were converted to N-sulfonyl monocyclic β-lactams by treatment with four different sulfonyl chlorides in the presence of Et(3)N and 4,4-dimethyl-aminopyridine (DMAP).